2019
DOI: 10.1088/1361-6595/ab08af
|View full text |Cite
|
Sign up to set email alerts
|

Numerical studies of the ExB electron drift instability in Hall thrusters

Abstract: The properties of the ExB drift mode in Hall thrusters were investigated through particle-based simulations. Two different two-dimensional models coupling the ExB drift azimuthal direction with the axial accelerating field and radial magnetic field directions, respectively, were implemented assuming Cartesian slab geometry. While the azimuthal-axial model is selfsustaining through the closure of the anode-cathode circuit, the radial-azimuthal one is equipped with an injection system that preserves the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…This code has been benchmarked with other codes through the 2D axial-azimuthal benchmark by Charoy et al [33] and tested for other instability cases [36,61] 4.1.5. ISTP The 2D PIC code [18] developed at ISTP is a combination of previous 1D-radial [62,63,64] and 1D-azimuthal [30] PIC codes. The code is written in Fortran90 and it uses a structured, uniform, rectangular grid.…”
Section: Stanfordmentioning
confidence: 99%
“…This code has been benchmarked with other codes through the 2D axial-azimuthal benchmark by Charoy et al [33] and tested for other instability cases [36,61] 4.1.5. ISTP The 2D PIC code [18] developed at ISTP is a combination of previous 1D-radial [62,63,64] and 1D-azimuthal [30] PIC codes. The code is written in Fortran90 and it uses a structured, uniform, rectangular grid.…”
Section: Stanfordmentioning
confidence: 99%
“…Secondly, short wavelength instabilities with a significantly large component along the magnetic field reduce to the unmagnetized (ion-sound) form as seen from the analytical solution of the dispersion relation. Recent models (Héron-Adam 2013, Hara-Cho 2017, Croes et al 2017, Jahnunen et al 2018b, Tavant et al 2018, Taccogna et al 2019 have added the radial coordinate resolving the direction along the magnetic field and accounting for the sheath boundary conditions. They have shown that the full ion sound regime is not realized, but a more effective regime of discrete cyclotron resonance instabilities (again inverse cascade towards low wavenumbers) occur.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Another important aspect that these models can handle is the coupling between SEE and ExB EDI assessing the relative importance of these two phenomena on the electron anomalous transport. It has been recently shown (Tavant et al 2018, Taccogna et al 2019) that the electron radial heating due to ExB EDI can induce a larger SEE, but this, in turn, can help the ExB EDI saturation by cooling the electrons. As a result, it was observed that the anomalous electron cross-field mobility in the bulk plasma (induced by ExB EDI) decreases by 20% as the effective SEE coefficient increases.…”
Section: ____________________________________________________________mentioning
confidence: 99%
See 1 more Smart Citation
“…We assumed that neutral particles are spatially and temporally uniform with a Maxwellian velocity distribution at the gas temperature of 300 K, which is the common assumption for low-pressure plasma sources. [23][24][25] For the water neutralizer, H2O + , OH + , H + , H − , O − , OH − , and electrons were taken into account, whereas only Xe + and electrons were considered for the xenon neutralizer. The collision reactions and their cross sections for each neutralizer were the same as those employed in our previous papers (see Ref.…”
Section: A Calculationmentioning
confidence: 99%